Intraocular pressure and its determinants in a very old population: the ural very old study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Panda-Jonas, Songhomitra; Tuliakova, Azaliia M.; Fakhretdinova, Albina A.; Rusakova, Iulia A.; Jonas, Jost B. (Heliyon, 2024)
Purpose - To explore intraocular pressure (IOP) and its associated parameters in an aged population. - Methods - The epidemiologic Ural Very Old Study (UVOS) conducted in Bashkortostan/Russia included 1526 participants with an age of ≥85 years. Besides a whole series of ocular and systemic examinations, IOP was determined applying non-contact tonometry. Body mass index, diastolic blood pressure and age were the factors used to estimate the cerebrospinal fluid pressure (CSFP). - Results - The study consisted of 904 participants (age: 88.6 ± 2.7 years) with available IOP readings and without anti-glaucomatous therapy. Mean IOP was 14.5 ± 5.1 mmHg (median: 14 mm Hg; Q1:11; Q3:16; 95%CI:8,25) and 14.8 ± 4.6 mmHg (median: 14 mm Hg; Q1:12; Q3:17; 95%CI:8,28) in the right and left eyes, respectively. Higher IOP correlated (multivariable analysis; correlation coefficient r2:0.32) with female sex (P < 0.001), more sedentary lifestyle (P = 0.006), higher estimated CSFP (P < 0.001), higher total protein serum concentration (P < 0.001), stronger hand grip force (P = 0.01), thicker central cornea (P < 0.001), longer axial length (P = 0.01), absence of previous cataract surgery (P = 0.001), higher degree of pseudoexfoliation (P = 0.02, and thinner peripapillary retinal nerve fiber layer thickness (P = 0.004). Using this that model, IOP reading enlarged by 0.22 mmHg (95% CI: 0.09, 0.35) for each increase in estimated CSFP by 1 mm Hg, by 0.03 mm Hg (95% CI: 0.02,0.05) for each thickening in central corneal thickness by 1 μm, by 0.56 mm Hg (95%CI: 0.13,1.00) for each axial elongation by 1 mm, and by 0.40 mmHg (95% CI: 0.06,0.74) for each increase in the degree of pseudoexfoliation, and it decreased by 0.40 mmHg (95% CI: 0.06,0.74) by cataract surgery. - Conclusions - In this study population aged 85+years, IOP readings showed similar relationships as in younger study populations, including positive associations with higher estimated CSFP and longer axial length and a negative association with cataract surgery.
Online verfügbar: 9. Februar 2024, Artikelversion: 12. Februar 2024
Gesehen am 16.08.2024